(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Effective pain management is essential in dental care to ensure patient comfort and enhance treatment outcomes. This review explores various pharmacological and non-pharmacological pain management strategies employed in dentistry, including local anesthetics, non-opioid analgesics, sedation techniques, and psychological interventions. The utilization of these approaches is crucial in alleviating pain and anxiety during dental procedures, thereby improving patient satisfaction and treatment compliance. Additionally, considerations regarding the safety, efficacy, and patient-specific factors associated with each pain management modality are discussed. By integrating evidence-based pain management protocols and tailoring interventions to individual patient needs, dental professionals can create a more positive and comfortable dental experience while promoting optimal oral health outcomes.